Design and evaluation of mobile games to support active and reflective learning outdoors - Lonsdale, Peter (2011)
This thesis explores the use of situated, location-based mobile games for supporting learning in the field, to determine how these types of activity can support learners with reference to specific curricular aims, beyond just providing highly engaging and motivating activities. A software toolkit was developed to support the design and deployment of situated mobile learning activities. This was used to design and deploy mobile learning activities for two field studies. The first study used the critical incident technique to identify specific benefits and problems arising from outdoor mobile learning. We found that whilst learners were highly engaged by an outdoor learning activity facilitated by mobile devices, they were engaged only in the surface level of the activity and did not reflect on what they were doing. The second study comprised a grounded theory analysis of learner behaviour in the context of a location-based, enquiry-led learning game designed to overcome the problems found in Study 1 and in other projects. We present an analysis of learner interactions with the environment during an enquiry-led learning activity. Compared to an equivalent paper-based activity, the game helped to coordinate the learners’ activities and unexpected results from game actions prompted learners to reflect on their actions and what they observed. The physical environment also prompted discussion and reflection, but we saw specific problems arising from learners becoming distracted by their previous experience of the environment and by the proximity of environmental features. We discuss these findings and present implications for the design of future mobile learning games.